Behavioral Determinants of Infection Control: Evaluating Hand Hygiene Knowledge and Motivation in Critical Care Nurses - Citra Fiona Lutfi Nafisatunisa; Kholid Rosyidi Muhammad Nur; Dodi Wijaya; Masmuhul Khoir (KHD Production, 2026)
Strict adherence to the World Health Organization's Five Moments for Hand Hygiene is critical for preventing healthcare-associated infections, especially in High Care Units where vulnerable patients face elevated risks. This study aimed to evaluate the knowledge, attitudes, and motivation regarding hand hygiene protocols among intensive care nurses. A quantitative descriptive design with a case study approach was utilized at the high care unit. Researchers selected participants through specific inclusion and exclusion criteria to ensure appropriate representation. A validated structured questionnaire measured cognitive understanding, psychological dispositions, and internal drive concerning the five moments and six-step handwashing procedures. Quantitative analysis revealed a significant disparity between psychological readiness and technical comprehension among the clinical staff. Sixty percent of nursing personnel demonstrated poor knowledge of standard handwashing protocols and critical moments of transmission. All respondents exhibited universally positive attitudes and strong intrinsic motivation toward infection prevention practices. A critical gap exists between nurses' favorable psychological dispositions and their actual cognitive grasp of evidence-based hygiene guidelines. Hospital administrators must implement targeted educational interventions and robust supervisory frameworks to bridge this cognitive deficit. Translating high motivation and positive attitudes into consistent clinical execution requires continuous professional development. Ultimately, structural support and ongoing evaluation remain essential to elevate patient safety outcomes in intensive care environments.